Assessment of the quality of general movements in newborn infants: a tool to predict developmental disorders at an early age - Ahmad Suryawan; Bambang Permono; Komang Ayu Witarini; Risa Etika; Fatimah lndarso; Moersintowarti B. Narendra (Indonesian Pediatric Society, 2008)
Background Nowadays, quality assessment of general movements(GMs) in infants can be used as a tool to predict developmentaloutcome. Until now, there is no published study in this field inIndonesia.Objectives The aim of this study was to evaluate the quality ofGMs of newborn infants.Methods A prospective study was done at neonatal ward, Dr.Soetomo Hospital in Surabaya, between December 2006 andJanuary 2007. A single supine position video recording of newbornsat GMs preterm and writhing age was made using Precthl's method.Infants were chosen consecutively among singletons above 28week gestational age. The quality of GMs was assessed by meansof Gestalt perception by one of the authors, who had been trainedand certified in GMs. GMs were classified into: normal-optimal,normal-suboptimal, mildly-abnormal, and definitely-abnormal.Correlation tests were used to assess the relationship betweenperinatal conditions and the quality of GMs.Results 106 videos were recorded, and 100 were assessedcompletely. Abnormal GMs were found in both 35 pretermage (normal-optimal 2.9%; normal-suboptimal 28.6%; mildly-abnormal45. 7o/o; definitely-abnormal22.9o/o) and 65 writhing age(3.1 o/o; 41.5%; 41.5%; 13.8%, respectively) (P=0.285). There wasa weak negative correlation between birth weight and the qualityofGMs (r=-0.20, P=0.044).Conclusions The quality ofGMs in Indonesian newborn infants inour study was predominantly abnormal, which puts these infantsat high risk for later developmental disorders. The lower theinfants'birth weight, the more likely for abnormal GMs.